2020
DOI: 10.1186/s12884-020-03371-3
|View full text |Cite
|
Sign up to set email alerts
|

Association between maternal cannabis use and birth outcomes: an observational study

Abstract: Background As cannabis consumption is increasing globally, including among pregnant women, there is a critical need to understand the effects of cannabis on fetal development and birth outcomes. We had two objectives: to determine 1) the factors associated with self-reported cannabis use in the pre/early-pregnancy period, and 2) whether cannabis use is associated with low birth weight, preterm birth, or small size for gestational age (GA) infants. Methods … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
25
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(27 citation statements)
references
References 22 publications
2
25
0
Order By: Relevance
“…As few studies reported quantity, we used the classification of cannabis dependence or abuse or substance use disorder associated with cannabis as a proxy for intensive use. Only one study reported medical use, and the only pregnant women with medical use was excluded 24 . Therefore, we were not able to conduct this subgroup analyses.…”
Section: Data Synthesismentioning
confidence: 99%
See 2 more Smart Citations
“…As few studies reported quantity, we used the classification of cannabis dependence or abuse or substance use disorder associated with cannabis as a proxy for intensive use. Only one study reported medical use, and the only pregnant women with medical use was excluded 24 . Therefore, we were not able to conduct this subgroup analyses.…”
Section: Data Synthesismentioning
confidence: 99%
“…Most studies did not present information regarding the type of cannabis use (medical or recreational use). Only three studies clearly stated that cannabis use was recreational 24,29,30 . The great majority of studies relied only on maternal self-report (n=14).…”
Section: Accepted Manuscriptmentioning
confidence: 99%
See 1 more Smart Citation
“…Alarmingly, gestational exposure to cannabis can increase the risk for adverse neonatal outcomes, including low birth weight and preterm delivery [ 6 , 7 , 8 ]. However, these studies are confounded by that fact that cannabis users are more likely to concurrently abuse other drugs, such as alcohol and tobacco [ 9 ], highlighting the need for animal studies that focus on the effects of specific constituents of cannabis (i.e., Δ9-tetrahydrocannabinol [Δ9-THC] and cannabidiol [CBD]) on short- and long-term maternal-fetal outcomes [ 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…Alarmingly, gestational exposure to cannabis can increase the risk for adverse neonatal outcomes, including low birth weight and preterm delivery [6][7][8]. However, these studies are confounded by that fact that cannabis users are more likely to concurrently abuse other drugs such as alcohol and tobacco [9], highlighting the need for animal studies that focus on the effects of specific constituents of cannabis (i.e., Δ9tetrahydrocannabinol [Δ9-THC] and cannabidiol [CBD]) on short-and long-term maternal-fetal outcomes [9].…”
Section: Introductionmentioning
confidence: 99%